Two Distinct Aldolases of Class II Type in the Cyanoplasts and in the Cytosol of the Alga Cyanophora paradoxa. - Gross, W. (1994)
Two aldolases from the alga Cyanophora paradoxa (Glaucocystophyta) can be separated by chromatography on diethylaminoethyl-Fractogel. The two aldolases are inhibited by 1 mM ethylene-diaminetetraacetate (EDTA) and, therefore, are class II aldolases. When cells of C. paradoxa were fractionated, one aldolase was associated with the cytosol fraction and the other was associated with the cyanoplast fraction. The Km(fructose-1,6-bisphosphate) was 600 [mu]M for the cytosolic aldolase and 340 [mu]M for the cyanoplast aldolase. The activity of the cytosolic aldolase was increased up to 4-fold by 100 mM K+ and slightly inhibited by Li+ and Cs+, whereas the cyanoplast aldolase was not affected by these ions. Inactivation by 1 mM EDTA could be partly restored by the addition of Co2+ or Mn2+ and to a lesser extent by Zn2+ or Mg2+. The molecular masses of the native cytosolic and cyanoplast aldolases are about 90 and 85 kD, respectively, as estimated by velocity centrifugation in sucrose gradients. Implications for the evolution of class I and II aldolases in chloroplasts of higher plants and algae will be discussed.